PENGARUH TINGGI (RENDAHNYA) SKEPTISISME PROFESIONAL DALAM SUATU METODE BRAINSTORMING TIM AUDIT TERHADAP PENILAIAN TINGGI (RENDAHNYA) RISIKO KECURANGAN LAPORAN KEUANGAN - Ahmad Try Handoko (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
Professional skepticism is closely related to professional judgment in decision-making. Decision making is often a problem in the scope of financial statement audits. This is because there are different levels of individual professional skepticism. Therefore, this study aims to examine the effect of high (low) professional skepticism in an audit team brainstorming method on the assessment of high (low) risk of financial statement fraud. Professional skepticism and brainstorming methods are both important in producing an appropriate quality audit. This study applies a genuine experimental design with a factorial design with 64 Accounting students as respondents. Measurement of individual skepticism using the Hurtt (2010) scale, then these individuals were formed into a high professional skepticism audit team and a low professional skepticism audit team into 12 audit teams according to the number of samples. The audit team was tested using an open ended brainstorming method to assess the high (low) risk of financial statements in an audit case that the researcher had modified. The results of this study are based on the ordinal regression test conducted that there is no effect of high (low) professional skepticism in an audit team brainstorming method on the assessment of high (low) risk of financial statement fraud.